Technology trade with asymmetric tax regimes and heterogeneous labor markets: Implications for macro quantities and asset prices - Giuliano Curatola; Michael Donadelli; Patrick Grüning (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
The international diffusion of technology plays a key role in stimulating global growth and explaining co-movements of international equity returns. Existing empirical evidence suggests that countries are heterogeneous in their attitude toward innovation: Some countries rely more on technology adoption while other countries rely more on internal technology production. European countries that rely more on adoption are also typically characterized by lower fiscal policy exibility and higher labor market rigidity. We develop a two-country model, in which both countries rely on R&D and adoption, to study the shortand long-run effects of aggregate technology and adoption probability shocks on economic growth in the presence of the aforementioned asymmetries. Our framework suggests that an increase in the ability to adopt technology from abroad stimulates future economic growth in the country that benefits from higher adoption rates but the beneficial effects also spread to the foreign country. Moreover, it helps to explain the differences in macro quantities and equity returns observed in the international data.
Keywords: E3; F3; F4; G12; 330; Technology Adoption; R&D Investment; Asymmetric Tax Regimes; AssetPrices